Effect of light-curing techniques and preheated composite types as luting agents on lithium disilicate bond strength - Wanda Septya Ekatra; Tri Endra Untara; Diatri Nari Ratih (Majalah Kedokteran Gigi Indonesia, 2025)
he bond strength between lithium disilicate veneers and tooth structure depends on factors such as curing technique and luting agent. Preheated composite resins have been proposed as alternative luting agents due to their favorable mechanical and polymerization properties. This study aimed to evaluate the effects of conventional, ramp, and pulse light-curing techniques on the shear bond strength of lithium disilicate when preheated microhybrid and nanohybrid composite resins were used as luting agents.  Forty-two maxillary premolars were prepared and randomly assigned to six groups (n = 7) based on the combination of luting agent and light-curing technique: IA (microhybrid–conventional), IB (microhybrid–ramp), IC (microhybrid–pulse), IIA (nanohybrid–conventional), IIB (nanohybrid–ramp), and IIC (nanohybrid–pulse). Lithium disilicate veneers were cemented accordingly, and shear bond strength was evaluated. Results from a two-way ANOVA indicated a significant effect of the type of preheated composite resin on the shear bond strength of lithium disilicate (p < 0.05), while no significant effect of light-curing technique was observed (p > 0.05). This study confirmed that preheated microhybrid composite resin produces greater shear bond strength compared to preheated nanohybrid composite resin. Light-curing technique does not significantly affect the shearbond strength of lithium disilicate.